2015
DOI: 10.1186/s12936-014-0521-2
|View full text |Cite
|
Sign up to set email alerts
|

Randomized non-inferiority and safety trial of dihydroartemisin-piperaquine and artesunate-amodiaquine versus artemether-lumefantrine in the treatment of uncomplicated Plasmodium falciparum malaria in Cameroonian children

Abstract: BackgroundArtemether-lumefantrine and artesunate-amodiaquine are first-line treatment for uncomplicated malaria in Cameroon. No study has yet compared the efficacy of these drugs following the WHO recommended 42-day follow-up period. The goal of this study was to compare the clinical efficacy, tolerability and safety of artesunate-amodiaquine (ASAQ), artemether-lumefantrine (AL) and dihydroartemisinin piperaquine (DHAP) among children aged less than ten years in two malaria-endemic ecological regions of Camero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 17 publications
6
42
3
Order By: Relevance
“…DHA–PQQ was adopted as a second-line treatment in Kenya in 2009 [19]. Equally, research in west, south and central Africa has shown similar results [2022]. Dihydroartemisinin has been identified as a potent derivative of the parent drug artemether [4].…”
Section: Discussionmentioning
confidence: 99%
“…DHA–PQQ was adopted as a second-line treatment in Kenya in 2009 [19]. Equally, research in west, south and central Africa has shown similar results [2022]. Dihydroartemisinin has been identified as a potent derivative of the parent drug artemether [4].…”
Section: Discussionmentioning
confidence: 99%
“…In Africa, where virtually all ACTs recommended as first-line treatments of uncomplicated infections by the World Health Organization (WHO) 14,15 are readily available, a commonly used ACT alongside AL and AA is dihydroartemisininpiperaquine (DHP) which has been shown to be an efficacious treatment of uncomplicated falciparum malaria in Africa and elsewhere. [16][17][18][19][20] The efficacies of AL, AA, and DHP in single studies have been less frequently evaluated exclusively in < 5year-old malarious children.…”
Section: Introductionmentioning
confidence: 99%
“…These ADRs were not serious enough to discontinue anti-malarial treatments except for individuals in studies that reported serious adverse events such as jaundice, haemoglobulinuria, anaemia, convulsion, severe fatigue, severe malaria and deaths. In the current review, 3 study participant died during treatment [26]. This rate of mortality was not related to the study drugs on patients included in the study with uncomplicated malaria.…”
Section: Discussionmentioning
confidence: 82%
“…The search of studies published from 2004 to 2020 identi ed 13 articles important to the topic under review [22][23][24][25][26][27][28][29][30][31][32][33][34], out of which 10 were RCTs [22-30, 33, 34] and 3 non-comparative clinical trials without randomisation [31, 32] (Additional le 1). Data from 3 unpublished studies that were conducted by the Cameroon National Malaria Control Programme and independent researchers were also included in this review.…”
Section: Qualitative Synthesismentioning
confidence: 99%
See 1 more Smart Citation